Investor Commitment to Responsible Investing and Investee ESG Disclosure - Isidro, H.; Dirk E. Black; Marques, A. (Research Seminar, 2025)
We examine whether investors’ commitment to socially responsible investment principles influence their investee firms’ public disclosure of environmental, social, and governance (ESG) information. We find that following institutional investors’ public commitment to the United Nations Principles for Responsible Investment (PRI), investees’ ESG disclosure in U.S. Securities and Exchange Commission reports increases. We identify two mechanisms through which PRI investors influence investee firms’ ESG disclosure: submitting shareholder proposals that request enhanced sustainability disclosure and engaging directly with investee firms to encourage greater ESG disclosure. Our conclusions are robust to considering: 1) Alternative measures of ESG disclosure; 2) The level of institutional ownership of the firm by PRI investors before they join the PRI initiative and by other investors; 3) The ESG performance of the investee firm, using alternative ESG score providers; 4) The simultaneous estimation of institutional investment decision, firm ESG performance, and firm ESG disclosure; and, 5) An event triggering institutional investor demand for environmental information - the BP Deepwater Horizon oil spill. We also find that the improvement in firms’ ESG disclosure is attributable primarily to PRI institutional investors from Europe and is not driven only by large influential institutional investors. Overall, our analysis suggests that investors’ public commitment to social responsibility plays a crucial role in enhancing investee firms’ public disclosure of ESG information.